The Washington manual of surgical pathology - Humphrey, Peter A.; Dehner, Louis P., 1940-; Pfeifer, John D. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Healt h, 2012)
"The aim of this book is to provide a practical manual that is helpf ul to pathologists and residents in the daily practice of surgical path ology. The text encompasses all anatomic sites in the human body. Eac h chapter covers tissue handling, gross examination, gross dissection a nd diagnosis, processing, slide preparation, microscopic diagnosis, spe cial studies, and diagnostic reporting. The format of the book would be modeled after the Washington Manuals for other specialties (such as Me dical Therapeutics, Oncology, and Surgery)"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Pathology, Surgical